Fostering the professional development of Saudi female students: implications for educators in apparel and textiles programs in Saudi Arabia - Alzahrani, Sarah G. (Kansas State University, 2015)
Today, home economics in Saudi Arabia, in particular, apparel and textiles programs (AT) typically emphasize two major areas: apparel design and textile science. However, AT programs in Saudi Arabia need to evolve to help students take advantage of new job opportunities in the apparel retail sector. Establishing an apparel merchandising track in AT programs in Saudi Arabia will provide women with better preparation to succeed in the industry. Until recently, most female graduates of home economics programs in Saudi Arabia were prepared for teaching positions. The purpose of this study was to develop an apparel merchandising program for the AT discipline in Saudi Arabia. Qualitative data were collected in three phases to examine the focal points of choosing the new curricula: (a) the nature of the subject matter, (b) the nature of society, and (c) the nature of individuals. In Phase 1, the content of the top apparel merchandising programs in the US was examined to explore the nature of the subject matter. In Phase 2, the perceptions of industry professionals in Saudi Arabia were explored by interviewing 21 human resource managers and apparel store managers. Finally, the AT students’ needs to succeed in the apparel industry were examined by interviewing 17 female students. The data were analyzed by utilizing the word-based technique as well as comparing and contrasting responses to each question. The findings for all three phases were combined and compared to identify the knowledge and skills that need to be added to the new apparel merchandising track for AT discipline in Saudi Arabia. Results of the study indicated that all three phases reported the importance of considering hard skills, or content and process knowledge, and soft skills, or professional attitude and skills, in preparing AT student for the apparel retail industry. AT major knowledge, business knowledge, mathematics, as well as professional skills (e.g., communication, commitment, teamwork, English language, lifelong learning, and experience) are found to be essential for the success of Saudi women in the apparel retail industry. For AT educators in Saudi Arabia, this knowledge and skills have to be addressed in the apparel merchandising program.
Keywords: Apparel merchandising; Apparel education; Apparel retail industry; Saudi Arabia; Professional development; Female students' success; Higher Education (0745); Middle Eastern Studies (0555); Women's Studies (0453)